The data availability landscape in seven sub-Saharan African countries and its role in strengthening sugar-sweetened beverage taxation. Issue 1 (1st January 2021) - Erzse, Agnes; Abdool Karim, Safura; Thow, Anne Marie; Ahaibwe, Gemma; Amukugo, Hans Justus; Asiki, Gershim; Gaogane, Lebogang; Mukanu, Mulenga M.; Ngoma, Twalib; Ruhara, Charles Mulindabigwi; Wanjohi, Milkah N; Hofman, Karen
ABSTRACT: Background : Credible data and indicators are necessary for country-specific evidence to support the design, implementation, monitoring and evaluation of sugar-sweetened beverage (SSB) taxation. Objective : A cross-country analysis was undertaken in seven Sub-Saharan African countries to describe the potential role of available data in strengthening SSB taxation. The objectives were to: document currently available data sources; report on public access; discuss strengths and limitations for use in monitoring SSB taxation; describe policy maker's data needs, and propose improvements in data collection. Methods : The study used a mixed-methods approach involving a secondary data analysis of publicly available documents, and a qualitative exploration of the data needs of policy makers' using primary data. Findings were synthesised and assessed for data strengths and weaknesses, including usability and availability. SSB taxation-related data availability was critically assessed with respect to adequacy in strengthening taxation policy on SSBs. Results : Findings showed a paucity of SSB taxation-related data in all seven countries. National survey data are inadequate regarding the intake of SSBs and household expenditure on SSBs. Fiscal data from SSB tax revenue, value added tax from SSB sales, corporate income tax from SSB companies and SSB custom duty revenues, are lacking. Accurate information on the soft drink industry is not easily accessed. Conclusion : Timely, easily understood, concise, and locally relevant evidence is needed in order to inform policy development on SSBs. The relevant data are drawn from multiple sectors. Cross- sector collaboration is therefore needed. Indicators for SSBs should be developed and included in current data collection tools to ensure monitoring and evaluation for SSB taxation.